Patient-reported outcome: results of the multicenter German post-market study - Hasselbacher, Katrin; Maurer, Joachim T.; Sommer, Ulrich (European archives of oto-rhino-laryngology and head & neck, 2018)
Upper airway stimulation (UAS) is an alternative second-line treatment option for patients with obstructive sleep apnea (OSA). In our substudy of a previous multicentre study of patients implanted with UAS, we focused on patient-related outcomes like Epworth Sleepiness Scale (ESS), the Functional Outcomes of Sleep Questionnaire (FOSQ), snoring and personal satisfaction 6 and 12 months after the implantation.
Gesehen am 21.10.2020